Nitrogen gas flushing can be bactericidal: the temperature-dependent destiny of Bacillus weihenstephanensis KBAB4 under a pure N2 atmosphere - Munsch-Alatossava, Patricia; Alatossava, Tapani (Frontiers in Microbiology, 2014)
Tremendous food spoilage on one side and increased concern about the incidence of food-borne pathogens on the other side urge the development of additional steps to ensure food safety and quality. In previous studies, nitrogen (N2) gas flushing treatments of raw and pasteurized milk at cold chain-temperatures inhibited bacterial spoilage and highlighted different susceptibilities to the N2 treatment with the exclusion of certain bacterial types. Gram-negative Pseudomonas and Gram-positive Bacillus are the most common spoilage bacteria in raw and pasteurised milk, respectively. Here, we investigated the effects of pure N2 gas flushing on representative strains of these genera grown in mono- or co-cultures at 15°C and 25°C. Bacillus weihenstephanensis, which is a frequent inhabitant of fluid dairy products, is represented by the genome-sequenced KBAB4 strain. Among Pseudomonas, P. tolaasii LMG 2342T and strain C1, a raw milk psychrotroph, were selected. The N2 gas flushing treatment revealed: 1) temperature-dependent responses; 2) inhibition of the growth of both pseudomonads; 3) emergence of small colony variants for B. weihenstephanensis strain KBAB4 at 15°C induced by the N2 treatment or when grown in co-culture with Pseudomonas strains; 4) N2 gas flushing modulates (suppressed or stimulated) bacterial antagonistic reactions in co-cultures; 5) most importantly, SEM and TEM analyses revealed that at 25°C the majority of the KBAB4 cells were killed by pure N2 gas flushing. This observation constitutes the first evidence that N2 gas flushing has bactericidal effects.